Pengaruh Kolkisin terhadap Keragaman Fenotipe secara In Vitro pada Tanaman Stevia (Stevia rebaudiana Bertoni) - Novitasari, Desty; Nisa, Chatimatun; Hardarani, Novia (Universitas Lambung Mangkurat, 2023)
Stevia (Stevia rebaudiana Bertoni) is a plant that produce low-calorie natural sweeteners that can be used as a substitute for sugar cane for people with Diabetes Mellitus (DM) and obesity. Improvements to the properties of stevia in order to produce low-calorie natural sweeteners are mostly carried out in the laboratory using in vitro techniques. The media used were Murashige and Skoog with the addition of IAA dan BAP. This study aims to determine the phenotypic diversity in stevia with the addition of various concentrations and duration of immersion of the mutagen in the form of colchicine and to find the best interaction treatment used. The study was in the form of a two-factor randomized block design, the first factor being various concentrations of colchicine, namely k0 = 0% as control, k1 = 0,03% and k2 = 0,05%. The second factor was the duration of colchicine immersion, namely t1 = 24 hours and t2 = 48 hours. The result of this study indicate that the interaction of concentration and duration of colchicine immersion has a significant effect on the percentage of contamination with a concentration of 0,05% treatment and 24 hours immersion as the best contamination percentage treatment of 12,50%. The highest percentage of live explants was treated with a 24 hours immersion period of 8,33% and the lowest percentage was found in the 48 hour immersion treatment at 0%. The lowest percentage of browning was in the 0,05% colchicine concentration treatment at 58,33% and the highest percentage was found in the 0,03% concentration colchicine treatment at 93,75%.